(untitled) (Revista Electrónica REDINE, 2018)
This work has as aim think about the innovation for the educational transformation, bearing in mind that the innovation contributes innovation to produce improvements in the educational process, without them it would be difficult to answer to the development of the knowledge on the learning, the education, the human development, the contents curriculares, and especially to the changeable conditions of the current company. The innovation there articulates the processes of formation, action and generation of knowledge, constituting a valuable modal for the capture of decisions on policies and educational practices that allow to improve the quality of the education. To advance towards a qualit education for all, to achieve the sustainable development, which propitiates the necessary changes to form to the company of the tomorrow. The work concludes with some reflections on the importance of the innovation for the educational transformation.